Geometry optimisation of a wave energy converter - Costa, Susana Maria Vicente da (2022)
The evolution of technology and its worldwide access has been key in the development of different scientific areas and in several socioeconomic advances. Both production and usage of these equipment and services require energy, which resulted in the growth of its demand and use, and also led to the emergence of environmental concerns regarding energy consumption and extraction, with a current political and social pressure towards the reduction of the consumption of fossil fuels and, consequently, its substitution for alternative sources. Among the alternative energy sources, marine renewable energy presents a high potential, in the form of wave, tidal, and ocean thermal energy. The progress of these renewable sources is greatly influenced, however, by increasing interest and financial investment on these technologies. Computational simulation of technological systems and processes, integrating optimisation algorithms, may be used as a tool to reduce the cost of structure development and increase their robustness, which will add value to new projects. This dissertation addresses the geometry optimisation of a point-absorber wave energy converter, focusing on the increase of energy absorption derived from heave forces. This process included the development of an initial geometry, which was evaluated in terms of hydrodynamics and optimised through an optimisation algorithm to tune the shape parameters that influence energy absorption with the goal of obtaining the optimal geometry. A deployment site in the Portuguese coast was defined to get information on the predominant waves for the assessment of several sea states. The used software is NEMOH and WEC-Sim, both open-source, for the evaluation of the interaction between the structure and the imposed wave conditions. The results that were extracted and analysed from this software included forces in the six degrees of freedom. Under extreme wave conditions, the highest increase in efficiency in wave energy conversion to mechanical energy between initial and final shapes was of around 20%, corresponding to an increase from 35.64% to 54.18%, while under average wave conditions, that increase only reached a value of around 2%, corresponding to an increase from 22.14% to 24.51%.